Reinventing government: the case of national service - Lenkowsky, Leslie; Perry, James L. (2000)
When Bill Clinton embraced national service as one of his administration's priorities, he took a step forward on two of his key initiatives. Not only was national service a new initiative in its own right, but Clinton also held it up as a model of his efforts to reinvent government. It would be an exemplar of government that is catalytic, competitive, decentralized, and results oriented. This case study examines the theory and reality of reinvention. The Corporation for National Service and its programs have come under fire for being more political than catalytic, being simultaneously too centralized and too decentralized, and pursuing too many unclear goals. This article seeks to identify discontinuities between the rhetoric and the reality of reinvention in this instance and draw lessons for public sector reform. - Reproduced
Keywords: Public administration - United States; Public administration